Experiments of dike-induced deformation: Insights on the long-term evolution of divergent plate boundaries - TRIPPANERA, DANIELE; RUCH, JOEL; ACOCELLA, Valerio; Rivalta, E. (Journal of Geophysical Research: Solid Earth, 2015)
The shallow transport of magma occurs through dikes causing surface deformation. Our understanding of the effects of diking at the surface is limited, especially on the long term, for repeated intrusive episodes. We use analogue models to study the upper crustal deformation induced by dikes. We insert metal plates within cohesive sand with three setups: in setup A, the intrusion rises upward with constant thickness and in setups B and C, the intrusion thickens at a fixed depth, with final rectangular (setup B) or triangular (setup C) shape in section. Setup A creates a doming delimited by reverse faults, with secondary apical graben, without close correspondence in nature. In setups B and C, a depression flanked by two uplifted areas is bordered by inward dipping normal faults propagating downward and, for deeper intrusions in setup B, also by inner faults, reverse at the surface; this deformation is similar to what is observed in nature, suggesting a consistent physical behavior. Dikes in nature initially propagate developing a mode I fracture at the tip, subsequently thickened by magma intrusion, without any host rock translation in the propagation direction (as in setup A). The deformation pattern in setups B and C depends on the intrusion depth and thickness, consistently to what is observed along divergent plate boundaries. The early deformation in setups B and C is similar to that from a single rifting episode (i.e., Lakagigar, Iceland, and Dabbahu, Afar), whereas the late stages resemble the structure of mature rifts (i.e., Krafla, Iceland), confirming diking as a major process in shaping divergent plate boundaries.